MOULTING OF PORTUNUS PELAGICUS LINNAEUS - Hamsa, K M S Ameer (Indian Journal of Fisheries, 2011)
Some of the interesting informations on the moulting of laboratory-reared crabs of Portunus pelagicus Linnaeus are given with illustrations